Caregiver Difficulties Scale (CDS): Translation and Psychometric Evaluation Among Iranian Mothers of Cerebral Palsy Children. Issue 1 (2nd January 2018) - Farajzadeh, Ata; Amini, Malek; Maroufizadeh, Saman; Wijesinghe, Champa J.
ABSTRACT: The aim of this study was to investigate of psychometric properties of the Caregiver Difficulties Scale (CDS) for Iranian caregivers of children with cerebral palsy (CP). After a forward-backward translation, the Persian version of CDS (P-CDS) was administered to 151 Iranian mothers of CP children. The confirmatory factor analysis (CFA) was applied to measure the factor structure of P-CDS. The reliability was evaluated by examining internal consistency and test-retest method over a 2-week period using Cronbach's alpha and the intraclass correlation coefficient (ICC), respectively. The construct validity was assessed by measuring the association between the scores of the P-CDS and Caregiver Burden Scale (CBS), World Health Organization Quality of Life (WHOQOL-BREF), the Beck Depression Index (BDI II), and the Fatigue Severity Scale (FSS). The fit indices showed that the original model of CDS wasrelatively adequate (χ 2 /df = 2.03, CFI = 0.90, TLI = 0.88 and RMSEA = 0.08). All domains of P-CDS met the minimum reliability standards (Cronbach'salpha and ICC > 0.7). All subscales of P-CDS were positively correlated with the CBS, BDI-II and FSS and negatively correlated with the WHOQOL-BREF. The results showed that P-CDS is a valid and reliable measure for assessing the burden of care in Iranian mothers of CP children.